Violent victimisation in Lagos metropolis: An empirical investigation of community and personal predictors - Adisa, Waziri B (International review of victimology, 2022)
Violence or its threats have been a part of many African cities since the end of the Cold War, when many African countries transited from military to civilian rule. While the incidence of organised crime and violent victimisation of innocent citizens is not new to many West African cities, the emergence of terrorist organisations, armed bandits, kidnappers and armed gangs in a city like Lagos has created new security challenges. The challenges include the inability of government to cope with the rising number of young people in organised cult clashes and the threats to peace and stability in Lagos metropolis. This study is designed to investigate the influence of socio-demographic (senatorial district, gender, age, ethnic group, marital status, education, employment, duration of residency and type of apartment) and community factors (presence of nightclubs/hotels, use of private security and frequency of police patrol) on residents’ experience of crime victimisation, robbery and organised crime. The study adopted a cross-sectional survey design and a quantitative method of data collection. A structured questionnaire was used to elicit information from 300 respondents across three senatorial districts of Lagos State. The study found that factors such as location, type of apartment, nightclubbing, duration of residence, employment status and use of private security predicted at least one of the three dependent variables. The implications of the findings are discussed.